2023
DOI: 10.22271/phyto.2023.v12.i1a.14557
|View full text |Cite
|
Sign up to set email alerts
|

A phytochemical and pharmacological review on Dalbergia sissoo: A potential medicinal plant

Abstract: Dalbergia sissoo plant, often known as the Bangladesh Shishu, is a member of the Fabaceae family. It widespread in Bangladesh, including Sylhet, Ranirhat, Isamoti, and Chittagong. It is also found in Afghanistan, Pakistan, India, and Nepal. This plant has been used to treat leukoderma, diarrhea, dyspepsia, ulcers, stomach disorders, itching, syphilis, scabies. This plant's extract comprised terpenoids, alkaloids, glycosides, flavanols, tannins, saponins, and glycosides. All segments of Dalbergia sissoo are ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The essential oil and extract of this plant are effective against Gram-negative bacteria, such as Pseudomonas aeruginosa and Escherichia coli , as well as Gram-positive bacteria including Bacillus subtilis and Listeria monocytogenes [ 27 ]. Furthermore, various phytochemical studies have shown the considerable existence of some polyphenolic compounds such as flavonoids [ 28 ] and tannoids and also the appearance of sterols, saponins, and triterpenes [ 29 , 30 ]. Among the reasons that allowed the development of the extract of Pistacia lentiscus leaf, either as an antioxidant agent or as an inhibitor of the enzymes responsible for diabetes to act as a trophic agent on the acinar tissue, to augment the production of enzymes of the cultured islets [ 31 ], there is first of all the absence of symptoms of toxicity, and then the abundance and wild growth of this species are additional aspects that qualify for a detailed study.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil and extract of this plant are effective against Gram-negative bacteria, such as Pseudomonas aeruginosa and Escherichia coli , as well as Gram-positive bacteria including Bacillus subtilis and Listeria monocytogenes [ 27 ]. Furthermore, various phytochemical studies have shown the considerable existence of some polyphenolic compounds such as flavonoids [ 28 ] and tannoids and also the appearance of sterols, saponins, and triterpenes [ 29 , 30 ]. Among the reasons that allowed the development of the extract of Pistacia lentiscus leaf, either as an antioxidant agent or as an inhibitor of the enzymes responsible for diabetes to act as a trophic agent on the acinar tissue, to augment the production of enzymes of the cultured islets [ 31 ], there is first of all the absence of symptoms of toxicity, and then the abundance and wild growth of this species are additional aspects that qualify for a detailed study.…”
Section: Introductionmentioning
confidence: 99%